Revisiting school days: retrospective experiences of ableism among autistic women and gender dissident individuals with late diagnosis - Garcia-Molina Irene; Sánchez-Padilla Raquel; Rodríguez Díaz Susana (Humanities & Social Sciences Communications)
Abstract Understanding how ableism manifests, particularly within the autistic community through the lens of gender-disability intersectionality, is crucial for improving educational practices. This study sought to explore the experiences of five Spanish autistic women and gender-dissident individuals with late diagnoses through qualitative, respectful, semi-structured interviews. Data were analyzed using Reflexive Thematic Analysis, and three main themes were constructed: (1) Internalizing the Label: From Attitudes to Practice—detailing what happened and how participants felt in response to the ableist attitudes and practices of peers and teachers; (2) The Schoolyard as Society’s Mirror—showcasing how broader societal tendencies are mirrored in school interactions; and (3) Invisibility of Needs, Invisibility of Identity—highlighting how participants felt different and went unnoticed by educational agents, which deeply impacted their sense of identity. Participants’ experiences of exclusion and stigma highlight the urgent need for more inclusive school environments that value diversity and actively support all students.